Misurare il tempo: tra fascino e sfide. Alle origini del calendario gregoriano - Sodi, Manlio (Saeculum Christianum. Pismo Historyczne, 2020)
The challenge concerning measuring time is as ancient as humanity. The problem of the accuracy of the calendar occupied outstanding scholars, but the results were always unsatisfactory. It was not until 1582 that at the times of Gregory XIII a precise calendar was created, which was the result of the scientific skills in various European countries. To identify some of the elements that underlie the Gregorian calendar is the purpose of this study, which examines the sense of measuring time that has been circulating around Easter for about three thousand years.